More answers

5x

Q: What is 2x 3x?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

2x - 3x = -x

3x + 2x - 8x + 2x = -x

2x+3x = 5x

2x+x is 3x

6x2+ 35xy + 11y2=6x2+ 33xy + 2xy + 11y2= 3x(2x + 11y) + y(2x + 11y)= (2x + 11y)*(3x + y) 6x2+ 35xy + 11y2=6x2+ 33xy + 2xy + 11y2= 3x(2x + 11y) + y(2x + 11y)= (2x + 11y)*(3x + y) 6x2+ 35xy + 11y2=6x2+ 33xy + 2xy + 11y2= 3x(2x + 11y) + y(2x + 11y)= (2x + 11y)*(3x + y) 6x2+ 35xy + 11y2=6x2+ 33xy + 2xy + 11y2= 3x(2x + 11y) + y(2x + 11y)= (2x + 11y)*(3x + y)

Related questions

2x + 3x = 5x.

2x - 3x = -x

2x + 3x = 5x

2x-3x = -1

3x + 2x - 8x + 2x = -x

No. 3x plus 2x = 5x. 3x multiplied by 2x = 6x²

2x+3x = 5x

If you mean: 3x-(2x+4x-6) then 3x-2x-4x+6 simplifies to 6-3x

3x - 3 = 2x + 6 3x = 2x + 9 x = 9

(2x x 3x) x 2 = 12x (2x times 3x times 2)

5x+7=3x-21 -7= -7 5x=3x-14 -3x=-3x 2x=-14 2x/2x=2x/-14 x=-7 The Answer Is -7 -

-3x(2x - 1)(2x + 1)